Transnational Reproduction : Race, Kinship, and Commercial Surrogacy in India - Deomampo, Daisy (Book collections on Project MUSE., 2016)
"Transnational Reproduction' traces the relationships among Western aspiring parents, Indian surrogates, and egg donors from around the world. In the early 2010s India was one of the top providers of surrogacy services in the world. Drawing on interviews with commissioning parents, surrogates, and egg donors as well as doctors and family members, it argues that while the surrogacy industry in India offers a clear example of 'stratified reproduction"--The ways in which political, economic, and social forces structure the conditions under which women carry out physical and social reproductive labour - it also complicates that concept as the various actors in this reproductive work struggle to understand their relationships to one another